Traditional New Year meals of Tuvans - Ondar, Asiana U. (The New Research of Tuva, 2015)
Article reviews the features of festival meals of Tuvans during the Shagaa – a New Year by the lunar calendar. It highlights the depiction of most significant and sacred meals – sheep head and sheep broad tail.
Keywords: meat; white meal; ritual meal; Buddhist altar; Tuvans; Shagaa